Labetalol and soluble endoglin aggravate bile acid retention in mice with ethinylestradiol-induced cholestasis - Cristina Igreja Sá, Ivone; Tripska, Katarina; Alaei Faradonbeh, Fatemeh; Hroch, Milos; Lastuvkova, Hana; Schreiberova, Jolana; Kacerovsky, Marian; Pericacho, Miguel; Nachtigal, Petr; Micuda, Stanislav (Frontiers in Pharmacology, 2023)
Labetalol is used for the therapy of hypertension in preeclampsia. Preeclampsia is characterized by high soluble endoglin (sEng) concentration in plasma and coincides with intrahepatic cholestasis during pregnancy (ICP), which threatens the fetus with the toxicity of cumulating bile acids (BA). Therefore, we hypothesized that both labetalol and increased sEng levels worsen BA cumulation in estrogen-induced cholestasis. C57BL/6J, transgenic mice overexpressing human sEng, and their wild-type littermates were administrated with ethinylestradiol (EE, 10 mg/kg s.c., the mice model of ICP) and labetalol (10 mg/kg s.c.) for five days with sample collection and analysis. Plasma was also taken from healthy pregnant women and patients with ICP. Administration of labetalol to mice with EE cholestasis aggravated the increase in BA plasma concentrations by induction of hepatic Mrp4 efflux transporter. Labetalol potentiated the increment of sEng plasma levels induced by estrogen. Increased plasma levels of sEng were also observed in patients with ICP. Moreover, increased plasma levels of human sEng in transgenic mice aggravated estrogen-induced cholestasis in labetalol-treated mice and increased BA concentration in plasma via enhanced reabsorption of BAs in the ileum due to the upregulation of the Asbt transporter. In conclusion, we demonstrated that labetalol increases plasma concentrations of BAs in estrogen-induced cholestasis, and sEng aggravates this retention. Importantly, increased sEng levels in experimental and clinical forms of ICPs might present a novel mechanism explaining the coincidence of ICP with preeclampsia. Our data encourage BA monitoring in the plasma of pregnant women with preeclampsia and labetalol therapy.